Kinesthetic Intelligence and Physical Literacy of Elementary School Students: A Case of Islamic Elementary School in Riau - Purnando, Riki; Sukarno, Sukarno; Rusmini, Rusmini (FKIP Universitas Lampung, 2022)
This study aims to provide an overview of the profile of kinaesthetic intelligence abilities and physical literacy abilities of students at Raudatul Athfal Al-Hidayah Tembilahan-Riau. The approach used in this research is quantitative with the sampling technique being total sampling. Based on the data that has been obtained followed by the discussion as described above, at the end of the study it can be concluded that the kinaesthetic intelligence profile of children in Raudatul Athfal Al-Hidayah in Tembilahan-Riau is dominated by children (students) with